Articulating Power: Strategic Narratives and Indonesia’s Imagined Role in a Multipolar World - Endiartia, Jacob Junian (The Eastasouth Journal of Social Science and Humanities, 2025)
This article investigates how strategic narratives articulated by domestic political elites shape national role conceptions in emerging powers. Focusing on the case of Indonesian political figure Anis Matta, the study employs an integrated framework combining Role Theory and Strategic Narrative Theory. Through textual analysis of Matta’s speeches and writings between 2014 and 2024, the article reveals a coherent narrative that reimagines Indonesia as a “peacemaker of civilisation” amid global disruption. It finds that narrative framing, moral positioning, and ideological continuity enable ideational elites to project new international roles prior to formal policy adoption. The study contributes to Foreign Policy Analysis by highlighting the discursive agency of non-executive actors in the pre-policy phase, offering insights into how emerging powers construct their foreign policy identities in an evolving multipolar order.